An Exploration of the Personal Non-Work Factors Affecting Employee Engagement When Working from Home - Krishnamoorthy, Raghu (Advances in Social Sciences Research Journal, 2022)
This paper reports on the research investigating the personal, non-work factors that influence the employee engagement of those working remotely from home. As corporations moved their workers to work from home because of the COVID-19 pandemic, the dynamics of work and the workplace evolved, with new, non-work-related human variables acquiring significance. Emerging research indicates that working from home is here to stay, making it necessary to understand and factor in those non-work elements in employee-related decision making. This exploratory qualitative study examines the crucial non-work elements influencing employee engagement based on the lived experiences of twenty-three employees who began working from home during the pandemic. Findings reveal that concerns about health, well-being, and work-life balance influence employee engagement when people work from home. The paper suggests that decision-makers look at the results of this study when answering important questions about the future of work and how things that do not have anything to do with work could affect how engaged employees are when they work from home.